The reproductive value as part of the shadow price of population - Gustav Feichtinger; Michael Kuhn; Alexia Prskawetz; Stefan Wrzaczek (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2011)
The reproductive value (see Fisher 1930) arises as part of the shadow price of the population in a large class of age-structured optimal control models.
Keywords: 330; Reproductive value; distributed optimal control theory; McKendrick equation; shadow price; indirect effect; Bevölkerungsentwicklung; Opportunitätskosten; Kontrolltheorie; Gesundheitsökonomik; Theorie